Did court uphold dismissal of free speech claim?. (20th September 2021) - Lyerly, Eric
Abstract : A student at Charter Oak State College enrolled in an online class titled "Communications 101." Two weeks into the course, the instructor asked the class to watch a video depicting a young man talking to and assisting an elderly disabled person.